Comment on “Computer algorithm can match physicians’ decisions about blood transfusions” - De Bruyne, Sander (Journal of translational medicine, 2021)
Of the 4946 patients who received intra-operative blood transfusions, 3604 cases were classified as appropriate and 1342 as inappropriate by expert anesthesiologists based on guidelines of the World Health Organization. In this study, no splitting procedure is described in the materials and methods section and it is stated that all 4946 data entries were inputted to the model. [...]as can be derived from the supplementary python script, it seems that the model was trained, validated and tested on exactly the same data entries. [...]the reported accuracies in this study are likely biased, have to be interpreted as the results of a potentially overfitted model and cannot be perceived as being per definition valid for independent data samples.